Reluctance to Use Photovoltaic Energy Technologies in Residential Buildings in Jeddah, Saudi Arabia: Reasons and Challenges - الجفري رعد (Journal of King Abdulaziz University: Environmental Design Sciences, 2025)
Research summary: This paper examines the phenomenon of reluctance to use photovoltaic energy in the residential sector in the city of Jeddah as a case study that also represents cities in the Kingdom of Saudi Arabia. It discusses the reasons for this reluctance of owners, what are the challenges they face, and what the future will be like for the residential sector in the city of Jeddah. The study passed through two balanced phases. The first phase included the researcher exploring the most prominent developments achieved by photovoltaic energy in the residential sector in terms of system components, costs, performance efficiency, and examining similar experiences in both Jordan and Malaysia. In the second stage, the researcher went to the photovoltaic energy system suppliers sector in the Saudi market and conducted focused meetings with them to confirm the residential sector’s reluctance to use photovoltaic energy and diagnose the reasons and challenges. In the third stage, the researcher designed a questionnaire according to what was achieved in the first and second stages, and the Al-Naseem neighborhood was chosen as a study sample representing the modern neighborhoods of Jeddah. The researcher concluded that the most important justifications and challenges of the study sample in not using photovoltaic panels/solar panels in the residential sector in the city of Jeddah were That photovoltaic energy panels (solar energy) have low effectiveness in producing electrical energy, and there is no financial support or incentives to invest in installing solar energy panels to produce the population’s electricity needs, and that photovoltaic energy panels (solar energy) do not provide the population’s needs of electricity. electricity. The study recommended providing effective awareness campaigns about the benefits and sustainability of using photovoltaic energy technologies to encourage residents to make sustainable decisions, and to support and motivate real estate owners and developers by providing financial and tax incentives to implement projects to install photovoltaic systems in buildings.